Can engagement in socially and cognitively stimulating leisure activities compensate for other dementia risk factors? A prospective cohort study. (31st December 2021) - Duffner, Lukas; Deckers, Kay; Cadar, Dorina; Steptoe, Andrew; de Vugt, Marjolein; Koehler, Sebastian
Abstract: Background: With the projected surge in global dementia cases, research is increasingly focusing on lifestyle factors as preventive measure. Social and cognitive leisure activities are promising targets, but have thus far received relatively little attention. This study investigates whether cognitive and social activities contribute to dementia risk, and whether engagement in these activities moderates the association between other known risk factors (education, wealth & lifestyle factors). Method: We used data of the English Longitudinal Study of Ageing (ELSA) on engagement in social and cognitive activities in 6346 participants, followed up from 2008/2009 until 2014/2015. Dementia prevalence was assessed until up to 7 years after baseline. Self‐reported cognitive (e.g. "reading the newspaper") and social (e.g. being a member of a social club) activities and social participation (e.g. "going to the cinema") were clustered into high and low based on a median split. We then assessed their individual contribution to dementia‐risk as well as their interaction with the other risk factors, using Cox regression models, controlling for age, sex, education, wealth and lifestyle risk factors Result: We found that higher engagement in cognitive (HR=0.476; 95% CI=0.27‐0.84) and social activities (HR=0.60; 95% CI=0.42‐0.87) as well as social participation (HR=0.59; 95% CI=0.38‐0.90) were associated with lower dementia risk, independently of the other risk‐factors in the model. We also found an interaction between the level of engagement in social activities and level of education with regard to dementia risk, but not with other risk factors. Conclusion: Cognitive and social leisure activities and social participation may be beneficial for overall dementia risk. The benefits of social activities may be larger for people with low education. Both should be taken into account when designing dementia prevention measures.